ROLE OF PHYSICAL FITNESS AND BODY COMPOSITION IN NAVAL CADETS: A NARRATIVE REVIEW - Gerasimos V. Grivas; Antonios Vantarakis (Scientific Publishing House. NSA Press, 2023)
Physical fitness is important to the general population, but for naval cadets, achieving a high level of physical fitness may be essential for success in their jobs. The purpose of this review was to summarize the current literature on physical fitness and body composition in naval cadets narratively and examine the effects of training programs on their physical fitness and body composition. The length of time that the personnel is on a ship cannot always be determined. For this reason, cadets must follow an exercise program to increase or maintain their physical condition during their voyages on a warship. This review revealed that endurance and strength training programs lasting 8 weeks to 12 months improved naval cadets' physical capacity, body composition, and BMI. In conclusion, this review provides practical suggestions for improving naval cadets' physical fitness and body.